Reproductive biology of the sea anemone shrimp Periclimenes rathbunae (Caridea, Palaemonidae, Pontoniinae), from the Caribbean coast of Costa Rica - Azofeifa-Solano, Juan Carlos (Zookeys, 2014)
Abstract. Caridean shrimps are a highly diverse group and many species form symbiotic relationships with different marine invertebrates. Periclimenes rathbunae is a brightly colored shrimp that lives predominantly in association with sea anemones. Information about the reproductive ecology of the species is scarce. Therefore, we collected 70 ovigerous females inhabiting the sun sea anemone Stichodactyla helianthus in coral reefs from the southern Caribbean coast of Costa Rica. Females produced on average 289 ± 120 embryos. The volume of recently-produced embryos was on average 0.038 mm(3), and embryo volume increased by 192% during the incubation period. The average embryo mortality during embryogenesis was 24%. The reproductive output was 0.24 ± 0.094, considerably higher than in many other pontoniine shrimps. Females carrying embryos close to hatching showed fully developed ovaries, suggesting consecutive spawning. We assume that the sheltered habitat, living on sea anemones, allows Periclimenes rathbunae to allocate more energy in embryo production than most other free-living caridean shrimps. This is the first record of Periclimenes rathbunae for Costa Rica.